The ECoaching Continuum for Educators : Using Technology to Enrich Professional Development and Improve Student Outcomes. - Rock, Marcia L. (Association for Supervision & Curriculum Development, 2019)
The book integrates best coaching practices with an account of how school professionals can use today's technologies to ensure that students are engaged and learning.